Cognitive impairment and electroencephalographic alterations before and after liver transplantation: What is reversible?. Issue 8 (August 2014) - Campagna, Francesca; Montagnese, Sara; Schiff, Sami; Biancardi, Anna; Mapelli, Daniela; Angeli, Paolo; Poci, Carlo; Cillo, Umberto; Merkel, Carlo; Gatta, Angelo; Amodio, Piero
<x xml:space="preserve">Abstract</x> The influence of liver transplantation (LT) on mental performance is debated, as is the role of pretransplant overt hepatic encephalopathy (OHE). The aim of this study was to evaluate the time course of the neuropsychological and electroencephalogram (EEG) features of patients with cirrhosis before and after LT with respect to prior OHE. The study population included 65 patients with cirrhosis on the transplant waiting list; 23 had a history of OHE. Each patient underwent an extensive psychometric assessment (10 tests, including paper and pencil tests and a computerized test) and an EEG before and 9 to 12 months after LT. For a subgroup of 11 patients, the assessment was also performed 3 and 6 months after LT. EEGs were analyzed spectrally, and the mean dominant frequencies were obtained. Both psychometric tests and EEGs improved 9 to 12 months after LT. Patients with a history of OHE before LT had worse cognitive performances (P < 0.001) and EEG performances in comparison with their counterparts with a negative history. They also showed greater cognitive improvement after LT (P < 0.01); however, their global cognitive performance remained slightly impaired (P < 0.01). After LT, EEGs normalized for 98% of the patients (P < 0.01), regardless of any history of OHE. In the subgroup of patients evaluated every 3 months, psychometric and EEG findings showed deterioration at 3 months and subsequently steady improvements from 6 months onward. In conclusion, both neuropsychological and EEG performances had significantly improved 1 year after LT. Patients with a history of OHE showed greater improvements after LT than patients with a negative history, but their global cognitive function remained slightly worse; in contrast, EEGs normalized in both groups. Liver Transpl 20:977‐986, 2014. © 2014 AASLD.